2014
DOI: 10.3892/mmr.2014.2711
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming human adipose tissue stem cells using epidermal keratinocyte extracts

Abstract: Human adipose tissue stem cells (ATSCs) can differentiate into various types of cell in response to lineage-specific induction factors. Reprogramming cells using nuclear and cytoplasmic extracts derived from another type of somatic cell is an effective method of producing specific types of differentiated cell. In the present study, the ability of reprogrammed ATSCs to acquire epidermal keratinocyte properties following transient exposure to epidermal keratinocyte extracts was demonstrated. Reversibly permeabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…The hADSCs exhibited favorable characteristics, including adherence, proliferation, and morphological changes indicative of differentiation into keratinocyte-like cells. These findings align with previous studies that have underscored the adaptability of ADSCs for regenerative applications in skin tissue engineering. The scaffold’s role in facilitating cell attachment, viability, and proliferation is pivotal for its success in tissue engineering. The high cell viability observed in the MTT assay indicates excellent biocompatibility and low cytotoxicity, essential for maintaining a conductive environment for cell growth and tissue regeneration.…”
Section: Discussionsupporting
confidence: 92%
“…The hADSCs exhibited favorable characteristics, including adherence, proliferation, and morphological changes indicative of differentiation into keratinocyte-like cells. These findings align with previous studies that have underscored the adaptability of ADSCs for regenerative applications in skin tissue engineering. The scaffold’s role in facilitating cell attachment, viability, and proliferation is pivotal for its success in tissue engineering. The high cell viability observed in the MTT assay indicates excellent biocompatibility and low cytotoxicity, essential for maintaining a conductive environment for cell growth and tissue regeneration.…”
Section: Discussionsupporting
confidence: 92%
“…The goal of regenerative medicine is to replace diseased tissues with functional cells or cellular products. Many studies have sought to generate KCs from fibroblasts [ 29 , 52 ], adipose tissue stem cells [ 53 ], and mesenchymal cells via reprogramming [ 54 ]. Due to its critical role in epidermal development [ 55 ], TP63 was once combined with other TFs and used for this purpose [ 29 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the same induction medium formulation was used for mouse ASC differentiation to a keratinocyte cell lineage (Shokrgozar et al, 2012). Other studies reported hASC differentiation to epithelial-like cells, but only following their exposure to retinoic acid supplemented culture medium (Chan et al, 2012;Yan et al, 2013), cocultivation with human foreskin keratinocytes in a Transwell culture system (Chavez-Munoz et al, 2013), or by reprogramming hASCs using nuclear and cytoplasmic extracts from epidermal keratinocytes (Xie et al, 2015).…”
Section: Discussionmentioning
confidence: 99%